analisis Penilaian Harga Saham pada Penawaran Saham Umum Kedua (Studi Kasus pada PT. Bank Negara indonesia Persero Tbk) - , Guntur Patrianto ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research aim to estimate an intrinsic value of BNI share when doing secondary public offering by using constant growth models and relative valuation. This research also used data of BNI financial statementâs during the last five year from 2002 until 2006. Method analysis of discounted cash flow conducted by : financial statement projection, growth rate, and value estimation. Relative valuation started with searching similar company in the same field of industry and chosening and specifying appropriate ratio or multiples from similar company. This Multiples used to convert a relevant book value variable from BNI become an estimation of market value. Multiples or ratio which used were : PER (Price Earning Ratio). The result from this research by using constant growth models obtained an intrinsic value estimation of BNI share at June 2007 range from Rp.1.162,26 up to Rp. 2.768,15. Result by using for the estimation of stocks price per share BNI by using PER equal from Rp. 1.611,60 up to Rp. 2.155,60. Based on this both approaching, price of BNI share at this time possibility fair.